Osteogenic properties of starch poly(e-caprolactone) (SPCL) fiber meshes loaded with osteoblast-like cells in a rat critical-sized cranial defect - Link, D. P. (2013)
Osteoblast-like cells together with a suitable scaffold can aid to the regeneration of bone defects. A suitable scaffold could be starch poly(ε-caprolactone) (SPCL) fiber meshes, which have shown a high potential to support bone formation in previous in vitro and in non-critical sized in vivo studies. The aim of this study was to assess the effect of these scaffolds alone or combined with osteoblast-like cells in the regeneration of a critical-sized cranial defect in male Fisher rats. Empty defects and defects filled with cell-free scaffolds were used as controls groups. Samples were analyzed by MicroCT and histological analyses. Histological analyses revealed that all study groups showed new bone formation from the defect edges towards the interior of the defects. Also, bone was formed in the center of the scaffolds, especially in the groups containing pre-loaded osteoblast-like cells. MicroCT reconstructions showed that bone formation increased over time and was enhanced with the inclusion of pre-loaded osteoblast-like cells compared to SPCL scaffolds alone. According to these results, the pre-loaded osteoblast-like cells contributed to the bone regeneration process in a critical-sized bone defect. Furthermore, SPCL fiber meshes proved to be an osteoconductive material to use for bone regeneration purposes.